THE DEVELOPMENT OF MATHEMATICS LEARNING INSTRUMEN THROUGH COOPERATIVE LEARNING WITH THE COMBINATION OF SCIENTIFIC AND REALISTIC - Rina Nur Afifa (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
The purpose of this research is to produce mathematics learning instrument through cooperative learnig model with the combination of scientific and realistic approaches which is valid, practical and effective. This researches is development research which focuses on developing Mathematic learning instrument through cooperative learning model with the combination of scientific and realistic approaches. The learning instruments produced in this research  were student books, students work sheets, lesson plan, and learning result test of rectangular and square material. While developing the learning instrument, the supported learning instrument were also developed. The developing model use in this research reffered to thiagarajan model or 4-D which consisted of defining step designing step, developing step, and disseminating step. The learning instrument produced in this researches were validated by two experts with the assessment is in very valid category and can be use with minor revision. The trial process was conducted once in this research. The trial was conducted in class VII c at SMPN 33 Bulukumba. The results of the trial test reveal that: (1) Mathematc learning nstrument through cooperative learning model with the combination of scientific and realistic approaches is already practical, but there are several advices from the  observers to improve the practicality of the learning instrument, (2) Mathematic learning instrument through cooperative learning model with the combination of scientific and realistic approaches is already effective because it has already fulfilled 3 of 4 effectiveness indicators, that the  completeness of classical learning result test had been achieved, the teacher ability in learning management is in high category, and the students responds is in positive category. By conducting the aforementioned development stages, it is obtained valid, practical, and effective mathematics learning instruments through cooperative learning model with the combination of scientific and realistic approaches